2022
DOI: 10.18632/aging.204443
|View full text |Cite
|
Sign up to set email alerts
|

SGOL2 promotes prostate cancer progression by inhibiting RAB1A ubiquitination

Abstract: Prostate cancer is the most prevalent genitourinary malignant cancer in men worldwide. Patients with prostate cancer who progress to castration-resistant prostate cancer (CRPC) or metastatic CRPC have significantly poorer survival. Advanced prostate cancer is a clinical challenge due to the lack of effective treatment strategies. In the field of oncology, SGOL2 was an emerging and differentially expressed molecule, which enhanced the proliferation of cell populations in vitro in our studies. Mass spectrum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Circulation of active Rabs can be mediated by guanine nucleotide exchange factors and GTPase‐activating proteins 24 . Rab1A can be regulated by miRNAs in colorectal cancer, prostate cancer, and hepatocellular carcinoma, or inhibited ubiquitination by SGOL2 in prostate cancer 25–28 . The oncogenic role of Rab1A via the mTOR signaling pathway has been preliminarily elucidated 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulation of active Rabs can be mediated by guanine nucleotide exchange factors and GTPase‐activating proteins 24 . Rab1A can be regulated by miRNAs in colorectal cancer, prostate cancer, and hepatocellular carcinoma, or inhibited ubiquitination by SGOL2 in prostate cancer 25–28 . The oncogenic role of Rab1A via the mTOR signaling pathway has been preliminarily elucidated 29 .…”
Section: Discussionmentioning
confidence: 99%
“…24 Rab1A can be regulated by miRNAs in colorectal cancer, prostate cancer, and hepatocellular carcinoma, or inhibited ubiquitination by SGOL2 in prostate cancer. [25][26][27][28] The oncogenic role of Rab1A via the mTOR signaling pathway has been preliminarily elucidated. 29 To the best of our knowledge, this is the first study to analyze the functional and mechanistical role of Rab1A in OSCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Initial research focused on the role of SGO2 in protecting centromeric cohesion during mammalian meiosis I, but subsequent studies found that high SGO2 expression is associated with poor prognosis in a variety of cancers, including liver cancer, prostate cancer, and glioma. [15,[30][31][32][33] By using cancer stem cell-associated genes (RAB10, TCOF1, and PSMD14), Liang et al constructed a prognostic model for HCC and identified SGO2 as a potential therapeutic target. [34] Deng et al used bioinformatics to verify the association between high SGO2 expression and poor overall survival and advanced clinicopathological features in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P4HB also served as a core role in the autophagy regulatory mechanisms of BLCA, warranting further investigation and exploration [19]. As the population ages over the coming decades, PRAD is one of the most common cancers in the urinary system, placing additional strain on the healthcare system [20][21][22][23][24][25][26]. Consistent with our pan-cancer analysis, our previous studies [8,27] found that P4HB expression was higher in tumor samples than in normal samples and P4HB downregulation could significantly inhibit the cell proliferation of six PRAD cell lines, including LNCap, C4-2, C4-2B, PC3, DU145 and 22RV1 cells.…”
Section: P4hb and Urinary Tumorsmentioning
confidence: 99%